Physiological characteristics of phytoplankton in response to different light environments in the Philippine Sea, Northwestern Pacific Ocean - Lee, Chang Hwa; Kang, Jae Joong; Min, Jun-Oh; Bae, Hyeonji; Kim, Yejin; Park, Sanghoon; Kim, Joonmin; Kim, Dongseon; Lee, Sang Heon (Frontiers in Marine Science, 2022)
The phytoplankton physiological status for determining the quantity and quality of the basic food sources in the marine ecosystem can be changed rapidly by ambient environmental conditions (e.g. light and nutrients). To understand the physiological characteristics of phytoplankton, phytoplankton community composition, pigment concentrations, primary production, and pigment production rates were estimated between 100% and 1% light depths in the Philippine Sea during the summer season of 2019. The dominant phytoplankton classes at the both light depths were Prochlorococcus and Synechococcus during the study period. The pigment concentrations except for photoprotective pigments (i.e. diadinoxanthin and zeaxanthin) were significantly higher (t-test, p < 0.05) at 1% light depths to increase light-harvesting efficiency. The production rates of these pigments had weak correlations with primary production at the 100% light depths, whereas they showed strong positive relationships at the 1% light depths. Moreover, all the photosynthetic pigments had a significantly fast turnover rate at the 100% light depths, compared to the 1% light depths, for the replacement of damaged PSII subunits from strong light. It suggests that the phytoplankton community, especially cyanobacteria (Prochlorococcus and Synechococcus) could not perform an optimal photosynthetic activity (i.e. primary production) due to high light intensity. Under the anticipated warming ocean scenario with a strong light exposure condition, cyanobacteria which would be the dominant phytoplankton could have a negative influence on primary production supporting the marine ecosystem.